Temperature Influences Pseudocapillaria tomentosa Infections in Zebrafish, Danio rerio (Hamilton 1822) - Connor Leong; Ruby Scanlon; Corbin J. Schuster; Michael L. Kent; Thomas J. Sharpton (Journal of Fish Diseases, 2026)
Poikilothermic organisms like fish are key economic drivers in aquaculture and the ornamental fish trade. Climate change impacts the health of fish because poikilothermic hosts experience the same temperature as their environment, making temperature a critical determinant of parasite infection dynamics. Pseudocapillaria tomentosa , a capillarid nematode infecting approximately 20% of zebrafish research facilities, provides an excellent model for investigating temperature effects on nematode development because zebrafish can tolerate a wide temperature range. We examined how water temperature influences egg development and worm maturation across the zebrafish's tolerable thermal range (13°C–35°C). Eggs held at 4°C or 13°C failed to larvate but resumed development when returned to 28°C. Larvation increased at 35°C, though infectivity was reduced in larval zebrafish. In adult zebrafish, cold water (13°C) slowed worm development for up to 3 months; only immature larvae were observed even at 102 days post‐exposure. Returning these fish to 28°C triggered rapid maturation, with gravid females appearing within 1 month. Conversely, fish held at 35°C had reduced worm burdens and arrested maturation compared to 28°C controls, with development resuming after temperature reduction. These findings align with field observations of seasonal P. tomentosa dynamics in temperate climates.

Pseudocapillaria tomentosa infections in laboratory larval and Adult Zebrafish (Danio rerio): Development and advances in an in vivo anthelmintic drug discovery model - Connor Leong; Ruby Scanlon; Aisling Kyne; Thomas J. Sharpton; Michael L. Kent (Veterinary Parasitology, 2026)

The Toxicology Investigators Consortium 2024 Annual Report - Kim Aldy; Shao Li; Mari Costantini; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; Michael Abesamis; Faiz Ahmed; Salman Ahsan; Peter Akpunonu; Adam Algren; et al. (Journal of Medical Toxicology, 2026)